Effect of water and methanol on the dissolution and gelatinization of corn starch in [MMIM][(MeO)HPO2]1. Issue 74 (13th August 2015) - Shen, Jianan; Wang, Leli; Men, Yongjun; Wu, Ying; Peng, Qiaohong; Wang, Xiaoling; Yang, Rui; Mahmood, Khalid; Liu, Zhengping
<x xml:space="preserve">Abstract</x> A small proportion of water or methanol in the complex solvents of IL ([MMIM][(MeO)HPO2])/water and IL ([MMIM][(MeO)HPO2])/water/methanol, respectively, could significantly accelerate the gelatinization/dissolution of corn starch.